PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 SIJUNJUNG - Nurfadillah, Nurfadillah; Harisman, Yulyanti; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTThe low learning outcomes of students in SMPN 11 Sijunjung as a background of this research. The purpose of this research is to know, what are the studentâs understanding of mathematical concept by using cooperative learning strategy give respects and matter better than student understanding of mathematical concept by using convensional. Type of the research is eksperimental research. The research population was a class VIII student of SMPN 11 Sijunjung academic year 2013/2014. Technique of random sampling, with a sample gradeÂ  VIII1 and VIII5. Data collection instrument was a test of understanding of mathematical concept. The test form used is an essay test were 8 items about the reliability of the test is r11 = 0,88. The techniques of data analysis were done to used the t-test a side. Based on hypothesisÂ  testing is obtained because tvalues > ttable. Then the hypothesis in this research was received. It can be concluded that the studentâs understanding of mathematical concepts that implement the cooperative learning strategy giving respect and matter technique better than studentâs understanding concept in convensional learning.